A novel teaching platform design with CAI for EM education. Issue 5 (28th June 2018) - Liu, Xianfeng; Sun, Kai; Yang, Deqiang; Pan, Jin; Zhang, Zhijun
Abstract: Computers and multimedia technology can greatly facilitate the visualization of abstract concepts and intangible objects such as electromagnetic waves. An educational design platform is proposed to assist undergraduate students in understanding these waves. At present, most electromagnetics courses still use traditional teaching design ideas, from mathematics to reason, and spend much time on formula deduction. Educational design overturns this idea thoroughly to learn with problems and solve experiments related to uncertain concepts; this design will help undergraduate students learn the basic characters of electromagnetic waves intuitively and more easily. Through the experiment‐simulation method, students can experimentally sample data and process data real‐time using simulation software. In this way, students can grasp the physical meaning of abstract concepts more accurately through experiments; furthermore, computer simulations can show the relationships between parameters more intuitively. Thus, the original intention of teaching aided design is exactly reflected: "see knowledge and learn knowledge."